“Timeless” workers? Risks, protection needs and opportunities - Vito Sandro Leccese (Labour & Law Issues)
The paper outlines the framework of a research project on “timeless” work. This concept refers to work arrangements in which the duration or temporal allocation of job performance is either not predetermined or is left to the worker’s discretion. The purpose of the research is to highlight how time may continue to constitute a significant variable, worthy of thorough examination, even in contexts where workers exercise substantial autonomy over the duration of their job performance. This relevance emerges not only in connection with the protection of workers’ health, but also in relation to work organisation and the determination of appropriate compensation.